Kualitas Implementasi Kurikulum dalam Pembelajaran - Abduloh Abduloh (Universitas Mathla'ul Anwar Banten, 2019)
The development of science and technology, at the moment is increasingly rapid. Therefore the world of education must be able to adapt it to the learning process, namely by implementing a curriculum to determine the quantity and quality of education outcomes, the good and bad results of education depend on